Geographic Labour Mobility and Unemployment Insurance in Europe - Konstantinos Tatsiramos (Institute for the Study of Labor (IZA), 2004)
Conventional wisdom suggests that unemployment benefits create a stronger geographic attachment by lowering the willingness of the unemployed to accept job offers. We assess empirically the effect of benefits on geographic labour mobility using individual data from the European Community Household Panel for France, Germany, Spain, and the UK. Contrary to the conventional wisdom, we find that receiving benefits enhances mobility offsetting the negative effect of benefits on the incentives to move. We estimate binary choice panel data models controlling for unobserved heterogeneity using random and fixed effects. The results are invariant to the estimated model.
Keywords: J65; J61; C25; C23; 330; geographic labour mobility; unemployment insurance; discrete choice panel data; Regionale Arbeitsmobilität; Arbeitslosenversicherung; Arbeitsuche; Schätzung; Frankreich; Deutschland; Spanien; Grossbritannien